Practice and procedure of the Inter-American Court of Human Rights - Pasqualucci, Jo M. (Cambridge : Cambridge University Press, 2013)
"In this thoroughly revised second edition that incorporates the major changes made in the procedures and practice of the Inter-American Court since the the original publication of this book, Jo M. Pasqualucci provides a comprehensive critique that is at once scholarly yet practical. She analyzes all aspects of the Court's advisory jurisdiction, contentious jurisdiction, and provisional measures orders through June 2012. She compares the practice and procedure of the Inter-American Court with that of the European Court of Human Rights, the International Court of Justice, and the United Nations Human Rights Committee. She discusses changes in the Rules of Procedure of the Inter-American Court that entered into force on January 1, 2010, and that substantially change the role of the Inter-American Commission in contentious cases before the Court. She also evaluates the challenges and means of State compliance with the Court's innovative reparations orders and describes several instances of State compliance and noncompliance"--Page [4] of cover.
Advisory practice and procedure -- Proceedings before the Inter-American Commission -- Jurisdiction of the Inter-American Court -- Proceedings on the merits : fact-finding and attribution of state responsibility -- Victim reparations -- Provisional measures -- State compliance with court-ordered reparations.
Includes bibliographical references (pages 389-400) and index.
Keywords: Inter-American Court of Human Rights -- Rules and practice; Inter-American Court of Human Rights; 2; Corte Interamericana de Derechos Humanos -- Reglas y reglamentos; International courts -- Rules and practice; Human rights -- America; Human rights; International courts; Rechtsprechung; Verfahrensrecht; Rechtsvergleich; Tribunales internacionales -- Reglas y reglamentos; Derechos humanos; America; Rules